جدید تہذیب میں ماتحتوں، غلاموں اور نوکروں کے ساتھ سلوک (شریعت کی روشنی میں): Treatment of subordinates, slaves, and servants in modern civilization (in the light of Shariah) - Dr. Hafiz Muhammad Ibrar Ullah; Rizwana Kousar; Dr Fatima (Al Manhal Research Journal, 2023)
In modern civilized societies, it is not considered bad for the owner to abuse the employee, even though the employee is very angry about it, but he is patient with tears of blood in his heart for fear of losing his job. Allah subhanahuwata’ala has placed a distinction between human beings to fulfill human needs, some are rulers and some are subjugated, some are masters and some are slaves, some are kings and some are subjects, some are rich and some are poor. It is a distribution from Allah. While taking ten hours of service from someone else is an easy task, providing one hour of service yourself is a very difficult task. In this regard, the example of the Holy Prophet (peace and blessings of Allah be upon him) is a guiding light for us that he honored his servants. In this regard, the moderate and middle way is what the Prophet (peace and blessings of Allah be upon him) treated with his subordinates, slaves, and servants, and the best way he treated them is a living example for us. An employee will sometimes think a lot in his heart, that he is a human being just like everyone else, and he also has the right to live, but he happily accepts all these things to support his wife and children. The difference in status is not to be considered a measure of superiority Rather, every human being has a quality.